2011
DOI: 10.2217/nnm.11.141
|View full text |Cite
|
Sign up to set email alerts
|

Improving Delivery and Efficacy of Nanomedicines in Solid Tumors: Role of Tumor Priming

Abstract: Effectiveness of nanomedicines in cancer therapy is limited in part by inadequate delivery and transport in tumor interstitium. This report reviews the experimental approaches to improve nanomedicines delivery and transport in solid tumors. These approaches include tumor vasculature normalization, interstitial fluid pressure modulation, enzymatic extracellular matrix degradation, and apoptosis-inducing tumor priming technology. We advocate the latter approach due to its ease and practicality (accomplished with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 76 publications
(104 reference statements)
1
68
1
1
Order By: Relevance
“…5); a similar pattern was reported by Tsukioka et al 26 Sclareol, methotrexate, dexamethasone and cisplatin did not modify micellar and liposomal doxorubicin accumulation and toxicity. Although paclitaxel has been shown to modify liposomal doxorubicin pharmacokinetics with selective doxorubicin tumor accumulation, 8 in our study, an enhanced doxorubicin accumulation was observed only with free doxorubicin (8. Conversely, mitoxantrone promoted the accumulation of free doxorubicin (12.1 nmol per mg of protein with the pretreatment vs. 4.3 without; Fig.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…5); a similar pattern was reported by Tsukioka et al 26 Sclareol, methotrexate, dexamethasone and cisplatin did not modify micellar and liposomal doxorubicin accumulation and toxicity. Although paclitaxel has been shown to modify liposomal doxorubicin pharmacokinetics with selective doxorubicin tumor accumulation, 8 in our study, an enhanced doxorubicin accumulation was observed only with free doxorubicin (8. Conversely, mitoxantrone promoted the accumulation of free doxorubicin (12.1 nmol per mg of protein with the pretreatment vs. 4.3 without; Fig.…”
Section: Introductioncontrasting
confidence: 54%
“…5,6 The chemotherapeutic priming as well as the increase in tumor blood flow have been used to selectively increase tumor drug penetration. 7,8 Spheroids, three dimensional architectures of cancer cells, are found in cancer patients with sizes of 250-750 μm. 9 Spheroids formed with cancer cell lines mimic both architecture and share the limited drug penetration properties since drugs are largely confined to the outer cell layers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations